Anti-GBM Disease in Pregnancy - Mohammed Muqeet Adnan MD; Jordan Morton MD; Syed Hashmi MD; Sufyan Abdul Mujeeb DO; William Kern MD; Benjamin D. Cowley MD (SAGE Publishing, 2015)
Antiglomerular basement membrane (GBM) disease presenting during pregnancy is uncommon. We present a case of a pregnant female who presented with acute renal failure requiring dialysis due to anti-GBM disease. She responded well to plasma exchange, high-dose steroids, and hemodialysis. Cyclophosphamide was discussed but not given at the patient's request due to concerns for the well-being of the fetus. Unfortunately, she suffered a spontaneous abortion in her eighth week of pregnancy. Subsequently, she had progressive improvement in her renal function and became hemodialysis independent at 2 weeks after diagnosis. Her renal function returned to baseline 3 months after diagnosis. We present this case in detail and review the literature regarding anti-GBM disease in pregnancy.